The role of Co(2+) in the crystallization of human SENP1 and comments on the limitations of automated refinement protocols - Rimsa, Vadim (International Union of Crystallography, 2011)
Metal ions often stabilize intermolecular contacts between macromolecules, thereby promoting crystallization. When interpreting a medium-resolution electron-density map of the catalytic domain of human sentrin-specific protease 1 (SENP1), a strong feature indicative of an ordered divalent cation was noted. This was assigned as Co(2+), an essential component of the crystallization mixture. The ion displays tetrahedral coordination by Glu430 and His640 from one molecule and the corresponding residues from a symmetry-related molecule. Analysis of the data derived from a previous structure of SENP1 suggested that Co(2+) had been overlooked and re-refinement supported this conclusion. High-throughput automated re-refinement protocols also failed to mark the Co(2+) position, supporting the requirement for the incorporation of as much information as possible to enhance the value of such protocols.